Metode Latihan Ekstrakurikuler Musik Tari di SMA Negeri 1 Talamau - fadil, Muhammad fadillah Delzon; Olan Yogha Pratama (EDUMUSIKA, 2024)
The aim of this research is to explain the methods of extracurricular dance music training at SMA Negeri 1 Talamau. This research adopts a qualitative approach using descriptive methods. The researcher acts as the main instrument, supported by writing tools and a camera as supporting instruments. Information was collected through literature searches, interviews, observations and documentation. The data analysis process involves data collection, data description, and data conclusion. Based on the research results, it was concluded that the music extracurricular (dance accompaniment) at SMA Negeri 1 Talamau was running quite well. Extracurricular coaches have solid expertise in music and dance. The training method applied has proven effective in increasing student progress at each meeting. Music activities (dance accompaniment) have become one of the main extracurricular activities at this school, are widely known by the community, and continue to receive research from the school. However, there are still several obstacles in carrying out this activity, especially related to obstacles in renewing the necessary musical instruments. This is of further concern to future researchers, because this can hinder the smooth running of extracurricular activities. However, this activity will continue to be celebrated every year as one of the permanent extracurricular activities at this school.